Lysosomes nor Mice Move Forward without Borcs7. Issue 10 (October 2018) - Joshi, Urjita; Houwman, Joseline A.; van der Sluijs, Peter
Abstract : Lysosome function and position in the cytoplasm depends on the BORCS machinery, which tethers lysosomes to the kinesin microtubule motor. A recent paper of Snouwaert et al . in Cell Reports characterizes a mouse with a spontaneous mutation in the Borcs7 subunit, which causes axonal dystrophy and impaired motor function.